Implementation of Moral and Religious Values in Early Childhood - Margaretha, Lydia; Haryono, Mimpira (CV Media Inti Teknologi, 2024)
This research aims to implement moral and religious values in early childhood. By using qualitative descriptive method. The research target comes from educators and education personnel at KB Gemilang Bengkulu City by looking at the habituation carried out by students and educators in the classroom. Data collection techniques are taken from observation, documentation and interviews. Technical implementation is carried out 15-20 minutes every day before the start of educational activities (primary observation) through lecture methods (explaining concepts), playing, telling stories, singing, modeling, role play, and traveling with material covering religious values such as the introduction of God. The results obtained through these routine activities can foster moral and religious values in early childhood.